Application model of surface removal contour to blade abrasive belt grinding. (2015) - Huang, Yun; Wang, Yajie; Li, Haining; Chen, Yaxiong; Yang, Zhongsheng
In order to improve dimensional accuracy of aero-engine blade edges, surface removal contour (SRC) model is applied to the engine blade grinding in this study. Firstly, according to variable curvature of characteristics the engine blades, this paper adopts the semi-Hertz contact theory to simulate grinding contact state. Secondly, surface removal contour model was deduced from the material removal rate (MRR) nonlinear model, and the model of the final grinding depth is proposed, and the model consider the influence of path interval. Thirdly, for determining the parameters of MRR nonlinear and linear model, abrasive belt grinding experiment is carried out, which shows the relative error of MRR nonlinear model to be -1.1↓~1.4↓. The application of abrasive belt grinding on the blade showed the maximum error of the processing is within 0.05 mm and the abrasive belt grinding process system is stable.